PENGARUH PROFITABILITAS, UKURAN PERUSAHAAN, DAN KEPEMILIKAN INSTITUSIONAL TERHADAP NILAI PERUSAHAAN MANUFAKTUR - Jeremy Stanley Pranoto, Herlin Tundjung Setijaningsih, Henny Wirianata (Fakultas Ekonomi, Universitas Tarumanagara, 2020)
The purpose of this research is to obtain empirical evidence abaout the effect of profitability, firm size, and institutional ownership on firm value. The population of this research is manufacturing companies listed in the Indonesia Stock Exchange (IDX) during the year 2015-2017. This research is conducted with a sample of 64 manufacturing companies. The data in this research is processed by Eviews version 10.0. the result of this research show that profitability, firm size, and institutional ownership has no effect on firm value.